The Analysis of Deixis on “Closed Doors” Song - Khanna Maulidia 'Ashr; Rawuh Yuda Yuwana (Universitas Musamus Merauke, 2023)
In this research, the author focuses on a pragmatic approach to the study of deixis analysis in the song